THE ANTECEDENTS OF DOUBLE-ENTRY. - Littleton, A. C. (The Accounting Review, 1927)
Abstract The article focuses on antecedents of double-entry in bookkeeping. It is proposed in this paper to follow the genealogy of bookkeeping back beyond those parental ancestors whose respectability was so ably proved at the time. The purpose here will be to trace out those blood-lines of preparental inheritance which finally converged at a certain time and place, there to confer certain characteristics upon the offspring. In trying to perceive the forces which produced double-entry, two questions, must be answered in the process. First, what were the antecedent elements out of which double-entry finally evolved. An answer is needed to this question, so that one may better appreciate how closely accounting has been, and still is, related to several collateral fields. Second, what surrounding conditions were necessary to give vitality to these antecedent elements? The antecedents of double-entry, those factors which in time became so interwoven as to render double-entry inevitable, are all familiar quantities; some of them are very old and some are very obvious, but all of them are, in the writer's opinion, indispensable. The art of writing is an indispensable antecedent, since bookkeeping is before all else a record; arithmetic is essential also, since bookkeeping is a sequence of simple computations, even though they are cast into certain forms; private property, since bookkeeping is concerned only with recording the facts about property and property rights.